Mechanisms Of Regulation Of Processes Of Moral Promotion In Media Space - Kamoliddin Turayev Samadovich (Periodica Journal, 2025)
The article discusses the importance of virtual existence and media literacy in the process of devaluation of moral norms that humanity faces as media capabilities expand. The article also discusses how active and interactive consumers or creators of information create different types of information with the help of media. They also provide insight into the methods of information delivery, subconscious signals hidden behind difficult to understand and disorganized materials, various methods and “codes” used by mass media and how they come into effect.
Keywords: virtual existence; media